CODE MIXING LANGUAGE INDONESIAN ENGLISH IN VIDEOS OF YUVI PHANâ€™S YOUTUBE CHANNEL - Adnyani Karang, Ni Putu Sri Widi (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTCode mixing is the process of mix two or more languages into one discourse or utterancein a particular situation. This study discussrs code mixing of Indonesian and Englishlanguage in videos of Yuvi Phan Youtube Channel, which aims to identify the types ofcode-mixing and describe the reasons for the usage of code-mixing that Yuvi Phan uses inher videos. The data were taken from two videos of Yuvi Phan Youtube Channel entitledâ€œkonspirasi teori penyebab dÃ©jÃ  vuâ€ and â€œmantul tips styling natural curls gampangâ€.Those data were collected using the documentation method by applying the note-takingtechnique. The theories used for the analysis are the theory of types of code-mixing byMuysken and reasons for using code-mixing by Hoffman. The findings of this studyindicate that all types of code-mixing are used in the videos. Those are 70 code-mixing forInsertion, 26 code-mixing for Alternation, and 50 for Congruent Lexicalization. In thisartcile, all of the reasons also appear in the code-mixing.Keywords: Code mixing, types of code mixing, Bilingual, Yuvi Phan.ABSTRAKPencampuran kode adalah proses mencampur dua atau lebih bahasa menjadi satu wacanaatau ucapan dalam situasi tertentu. Penelitian ini bertujuan untuk mengidentifikasi jenisjenispencampuran kode dan menjelaskan alasan penggunaan pencampuran kode yangdigunakan Yuvi Phan dalam videonya. Data tersebut diambil dari dua video ChannelYoutube Yuvi Phan berjudul "konspirasi teori penyebab deja vu" dan "mantul tips stylingnatural curls gampang". Data tersebut dikumpulkan menggunakan metode dokumentasidengan menerapkan teknik pencatatan. Teori yang digunakan untuk analisis adalah teorijenis pencampuran kode oleh Muysken dan alasan untuk menggunakan pencampuran kodeoleh Hoffman. Temuan penelitian ini menunjukkan bahwa semua jenis pencampuran kodedigunakan dalam video. Itu adalah 70 pencampuran kode untuk Penyisipan, 26pencampuran kode untuk Alternation, dan 50 untuk Leksikalisasi Kongruen. Di sinitermasuk semua alasan juga muncul dalam pencampuran kode.Kata kunci: Pencampuran kode, jenis pencampuran kode, Bilingual, Yuvi Phan